BEST PRACTICES DALAM PENERAPAN SISTEM INFORMASI MANAJEMEN DI SMA PGII 1 KOTA BANDUNG - Lisartika, Mia; Safwandy Nugraha, Mulyawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explore best practices in the implementation of Management Information Systems (MIS) at SMA PGII 1 Kota Bandung, as well as to identify the challenges faced during its implementation. The methodology employed is a qualitative approach with a case study method, involving direct observations and semi-structured interviews with the principal, teachers, and students. The findings indicate that strong management support, effective user training, adequate technological infrastructure, and transparent communication are key factors in the successful implementation of MIS. However, challenges such as resistance to change, limitations in system features, and dependence on technology still need to be addressed. This research recommends enhancing ongoing training, developing system features according to user needs, and applying change management strategies to overcome staff resistance. Additionally, it is essential to establish contingency plans for technology disruptions to ensure smooth learning processes. These findings are expected to provide valuable insights for other educational institutions in implementing similar systems and serve as a reference for policymakers in formulating more effective strategies for the adoption of information technology in educational settings.